CMX-2043 Mechanisms of Action In Vitro. Issue 3 (September 2016) - Lader, Alan S.; Baguisi, Alexander; Casale, Ralph; Kates, Steven A.; Beeuwkes, Reinier
Abstract : Abstract: α-Lipoic acid has been shown to provide cytoprotection in some tissues through antioxidant and antiapoptotic mechanisms. We have enhanced these properties by synthetic modification, resulting in a new chemical entity, CMX-2043, with proven efficacy in an animal model of cardiac ischemia-reperfusion injury. The present studies compare cytoprotective cellular pathways of R-α-lipoic acid and CMX-2043. Biochemical and cellular assays were used to compare antioxidant potency, tyrosine kinase activation, and protein kinase B (Akt) phosphorylation. CMX-2043 was more effective than lipoic acid in antioxidant effect, activation of insulin receptor kinase, soluble tyrosine kinase, and Akt phosphorylation. Activation of insulin-like growth factor 1 receptor was similar for both. CMX-2043 stimulation of Akt phosphorylation was abolished by the phosphatidylinositide 3-kinase inhibitor LY294002. Consistent with Akt activation, CMX-2043 reduced carbachol-induced calcium overload. The S-stereoisomer of CMX-2043 was less active in the biochemical assays than the R-isomer. These results are consistent with cytoprotection through activation of Akt and antioxidant action. CMX-2043 may thus provide a pharmacological approach to cytoprotection consistent with established anti-apoptotic mechanisms.